Shallow water benthic imaging and substrate characterization using recreational-grade sidescan-sonar. (March 2017) - Buscombe, Daniel
Abstract: In recent years, lightweight, inexpensive, vessel-mounted 'recreational grade' sonar systems have rapidly grown in popularity among aquatic scientists, for swath imaging of benthic substrates. To promote an ongoing 'democratization' of acoustical imaging of shallow water environments, methods to carry out geometric and radiometric correction and georectification of sonar echograms are presented, based on simplified models for sonar-target geometry and acoustic backscattering and attenuation in shallow water. Procedures are described for automated removal of the acoustic shadows, identification of bed-water interface for situations when the water is too turbid or turbulent for reliable depth echosounding, and for automated bed substrate classification based on singlebeam full-waveform analysis. These methods are encoded in an open-source and freely-available software package, which should further facilitate use of recreational-grade sidescan sonar, in a fully automated and objective manner. The sequential correction, mapping, and analysis steps are demonstrated using a data set from a shallow freshwater environment. Highlights: Recreational grade sonar has rapidly become popular among aquatic scientists. Processing routines are described that allow analysis of echosounder and sidescan data. Geometric and radiometric correction and georectification of sonar echograms. Simple models for shallow water sonar-target geometry and scattering/attenuation. This is encoded in open-source software to aid the democratization of the technology.